Study on Mollusk and Algae or Phytoplankton Community in Southeast Waters of Bali - Ulinuha, Devi; Perwira, Ima Yudha (Journal of Environment)
A study was carried out to observe the relation between mollusk with algae or phytoplankton in southeast waters of Bali. The study was conducted at Mertasari, Sindhu, Serangan, Purnama, and Kethewel beach. Shannon-Wiener diversity index was used to analyze the ecological condition, supported by analysis on water quality including dissolved oxygen (DO), biological oxygen demand 5 days (BOD5), water pH, and water salinity. There were 34 species of phytoplankton found in this study. The most predominant phytoplankton species in each beach were Navicula sp at Mertasari, Nitzschia sp at Sindhu, Pseudo-nitzschia sp at Purnama, Chaetoceros sp at Kethewel. Observation on macro algae showed that Ulva sp was to be the most predominant species in Serangan, Mertasari, and Sindhu beach (17.95, 16.25, and 17.81%). In mollusk observation, gastropod groups showed to be higher number than bivalve group. Nassarius sp showed to be the most predominant in Serangan beach (13.33%), while Ruditapes sp was predominant in Mertasari and Sindhu beach (11.59% and 14.81%). The highest diversity index of phytoplankton was shown by Kethewel beach (H = 1.35), while the lowest was shown by Shindu beach (H = 0.95). The highest diversity index of macroalgae was shown by Serangan beach which showed H = 2.08, while the lowest was shown by Purnama beach which showed H = 0.69. Serangan beach showed the highest diversity index (H = 2.72) with E = 0.66 compared to another locations, while Kethewel beach showed the lowest diversity index (H = 0.69 and E = 1). There was a relation between the existences of gastropod as the highest number of mollusk and Ulva sp as the gastropod feed.